Evolution of consumer protection law in the light of the proposal for a horizontal directive on consumer rights and Rome I regulation - Łuczak, Anna (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The aim of this paper is to give a broad analysis of changes in the field of consumer protection law in the European Union over three decades. In 2004, the European Commission launched a project of reviewing consumer law in order to strengthen consumers’ confidence in the internal market and to encourage businesses to conduct cross-border trading. The EU consumer protection regulatory framework is based on directives including a minimum harmonization clause. This clause allows Member States to maintain or adopt stricter consumer protection rules and leads to fragmentation in their national laws. For instance, it was found that the notion and definition of a consumer has been designed for use by a specific directive, depending on which area is covered by the regulation of the personal scope. The definition of the so-called weaker party in a contractual relationship is understood in a narrow way, which is highlighted in the established line of the European Court of Justice case law. A brief outline of the history of the shaping of consumer protection policy in the European Union is presented to demonstrate how the problem of amending consumer protection law has evolved in the EU as well as increased in importance; this has been demonstrated in several programs and resolutions of the European Parliament and communications of the European Commission, which discuss the need to reform consumer contract law.The Proposal for a Horizontal Directive on Consumer Rights is the result of a review of consumer law acquis communautaire, referred to as the Consumer Acquis, and aims at introducing a full harmonization clause where feasible.Until recently, the norms governing the determination of the law applicable to consumer contracts have been defined by the Rome Convention of 1980 on the law applicable to contract relations. Due to its overly casuistic nature and outdated provisions relating to consumer contracts, it was decided to amend the Convention, which was changed into the Rome I Regulation.
Keywords: ochrona prawna konsumentów; dyrektywa horyzontalna w sprawie praw konsumenta